Antimicrobial Peptides as Potential Antiviral Factors in Insect Antiviral Immune Response - Feng, Min; Fei, Shigang; Xia, Junming; Labropoulou, Vassiliki; Swevers, Luc; Sun, Jingchen (Frontiers in Immunology, 2020)
Antimicrobial peptides (AMPs) with antiviral activity (antiviral peptides: AVPs) have become a research hotspot and already show immense potential to become pharmaceutically available antiviral drugs. AVPs have exhibited huge potential in inhibiting viruses by targeting various stages of their life cycle. Insects are the most speciose group of animals that inhabit almost all ecosystems and habitats on the land and are a rich source of natural AMPs. However, insect AVP mining, functional research and drug development are still in their infancy. This review aims to summarize the currently validated insect AVPs, explore potential new insect AVPs and to discuss their possible mechanism of synthesis and action, with a view to providing clues to unravel the mechanisms of insect antiviral immunity and to develop insect AVP-derived antiviral drugs.